أسلوب الالتفات في شعر حسن السوسي ومفهومه: دراسة بلاغية تحليلية - نجية حسين محمد التهامي
This study discusses one of the rhetorical techniques used by Arab writers, which is the volta technique. This technique will be discussed in three anthologies of poems written by the Libyan poet Hassan Al-Sousy. Although it is significant in revealing the poetics and harmony of the literary text, the volta does not have an important place in the contemporary literary and critical studies because the study of volta in Arabic rhetoric was totally dedicated to the rhetoric of Holy Quran. Consequently, the main problem was analyzing the way Al-Sousy used this technique in his poems to express his feelings and convey the idea with its whole magnificence to the reader. The study aims at distinguishing, analyzing and discussing the different devices of volta in the poems discussed. By using both the descriptive analytical method and the inductive approach, the researcher aims at tracing the use of the volta technique from the perspective of previous rhetoricians and critics and connecting it to the contemporary perspectives in the poetics of poetry in order that her study occupies the place it deserves within the contemporary literary studies. For that reason, the researcher concentrated on the use of volta in the different subjective pronouns. Then, the researcher was to distinguish and analyse volta in verbs, between verbs and nouns, and between numbers and tools, in addition to volta in syntax and lexical structures. The outcome of this study confirmed that Al-Sousy as a poet has mastered his language through which he was able to strengthen interaction with the reader, influence the recipient of his poems and to identify with him in a way that makes the reader feels the sentiments and feelings of the poet. Al-Sousy succeeded in employing the volta technique in such a flexible and smooth way through using fluid rhetorical formulas with varied rhetorical speeches. For Al-Sousy, the volta technique was not just a writing tool, it was indeed a vibrant way that performs its role as a sign that gives poetry renewable aesthetic productivity. He wrote his poems with concealment that resulted from breaking the expectations of the reader and astonishing him/her by way of breaking the familiar rules and employing his stylistic qualifications through using such volta techniques. The use of such techniques created a magnificent difference that glamorized Al-Sousy’s poetic experience and served the underlying philosophical intent in his poems. The aesthetic variation in poetic lines and the conciseness in his volta techniques attracted the attention of the reader and enhanced him/her to digest the words, listening and contemplating them. The researcher recommends that the application studies be made on volta to include the Libyan literary production in poetry and prose as well.